2014
DOI: 10.1186/s12917-014-0257-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment in canine epilepsy – a systematic review

Abstract: BackgroundVarious antiepileptic drugs (AEDs) are used for the management of canine idiopathic epilepsy (IE). Information on their clinical efficacy remains limited. A systematic review was designed to evaluate existing evidence for the effectiveness of AEDs for presumptive canine IE. Electronic searches of PubMed and CAB Direct were carried out without date or language restrictions. Conference proceedings were also searched. Peer-reviewed full-length studies describing objectively the efficacy of AEDs in dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(120 citation statements)
references
References 40 publications
2
116
0
2
Order By: Relevance
“…Precisely, based on the controlled studies, direct AED comparisons include: Tipold et al (2014) showed that monotherapy with imepitoin in dogs with newly diagnosed epilepsy was almost similarly effective and potentially more tolerated than phenobarbital. The same result was reported within other studies investigated in the systematic review by Charalambous et al (2014).…”
Section: Appraisal Application and Reflectionsupporting
confidence: 79%
See 1 more Smart Citation
“…Precisely, based on the controlled studies, direct AED comparisons include: Tipold et al (2014) showed that monotherapy with imepitoin in dogs with newly diagnosed epilepsy was almost similarly effective and potentially more tolerated than phenobarbital. The same result was reported within other studies investigated in the systematic review by Charalambous et al (2014).…”
Section: Appraisal Application and Reflectionsupporting
confidence: 79%
“…Munana et al At this point it is worth mentioning that the international veterinary epilepsy task force (IVETF) recently published a consensus statement (Bhatti et al 2015) for treatment suggestions based mainly on current published evidence as provided and analyzed in this knowledge summary and in the systematic review by Charalambous et al (2014) and it was additionally supported and adjusted by expert's opinions.…”
Section: Primidone Vs Imepitoinmentioning
confidence: 99%
“…There is currently a lack of objective data regarding AED adverse-effect profiles (Charalambous and others 2014), hampering objective choice of AEDs based on both efficacy and adverse-effect profile. As such, there is a strong need for more objective studies of the adverse effects of drugs including PB and imepitoin.…”
Section: Introductionmentioning
confidence: 99%
“…These studies, however, were noted to carry a higher degree of bias 8. By allowing a decrease in the use of drugs metabolized by the liver, potassium bromide treatment also may decrease the frequency of hepatotoxicity.…”
Section: When Should a Second Aed Be Started And Which Should Be Used?mentioning
confidence: 99%